Beautiful Terrible Ruins : Detroit and the Anxiety of Decline - Apel, Dora (Rutgers University Press, 2015)
Once the manufacturing powerhouse of the nation, Detroit has become emblematic of failing cities everywhere-the paradigmatic city of ruins-and the epicenter of an explosive growth in images of urban decay. In Beautiful Terrible Ruins, art historian Dora Apel explores a wide array of these images, ranging from photography, advertising, and television, to documentaries, video games, and zombie and disaster films. Apel shows how Detroit has become pivotal to an expanding network of ruin imagery, imagery ultimately driven by a pervasive and growing cultural pessimism, a loss of faith in progress, and a deepening fear that worse times are coming. The images of Detroit's decay speak to the overarching anxieties of our era: increasing poverty, declining wages and social services, inadequate health care, unemployment, homelessness, and ecological disaster-in short, the failure of capitalism. Apel reveals how, through the aesthetic distancing of representation, the haunted beauty and fascination of ruin imagery, embodied by Detroit's abandoned downtown skyscrapers, empty urban spaces, decaying factories, and derelict neighborhoods help us to cope with our fears. But Apel warns that these images, while pleasurable, have little explanatory power, lulling us into seeing Detroit's deterioration as either inevitable or the city's own fault, and absolving the real agents of decline-corporate disinvestment and globalization. Beautiful Terrible Ruins helps us understand the ways that the pleasure and the horror of urban decay hold us in thrall.